151k views
5 votes
Simplify (2√27) x (3√32)

User AyCe
by
5.5k points

2 Answers

3 votes

Answer:

72√6

Explanation:

The expression to be simplified is (2√27)×(3√32)

Before that,


√(27)=√(9*3)= √(9)*√(3)=3√(3)


√(32)=√(16*2)= √(16)*√(3)=4√(3)

This implies that (2√27)×(3√32)


=(2*3√(3))*(3 *4√(2))


=6√(3)*12√(2)


=72√(6)

User Onur Gumus
by
5.4k points
5 votes

For this case we have the following expression:


(2 \sqrt {27}) (3 \sqrt {32})

We have to:


27: 3 * 3 * 3: 3 ^ 2 * 3\\32: 16 * 2: 4 ^ 2 * 2

Rewriting the expression and simplifying we have:


(2 \sqrt {3 ^ 2 * 3}) (3 \sqrt {4 ^ 2 * 2}) =\\(2 * 3 \sqrt {3}) (3 * 4 \sqrt {2}) =\\(6 \sqrt {3}) (12 \sqrt {2}) =\\72 \sqrt {3 * 2} =\\72 \sqrt {6}

Answer:


72 \sqrt {6}

User Jim Harte
by
5.1k points